The Ills of the Federal Sentencing Guidelines and the Search for a Cure: Using Sentence Entrapment to Combat Governmental Manipulation of Sentencing - Johnson, Robert S. (1996)
Consider the following scenario:' The police conduct an under- cover sting operation targeting drug traffickers. An undercover officer approaches a suspected drug dealer and arranges to purchase crack cocaine. Over a period of five weeks, the suspect makes seven sales to the officer, and the police arrest him after the final sale. The total amount sold by the defendant was 50.4 grams, just enough to place him within the mandatory minimum sentence of ten years. Had he sold up to 49.9 grams, his mandatory minimum sentence would only have been five years. The district court hearing this case found it not at all fortuitous that the agent arrested the defendant only after the agent had arranged enough successive buys to reach the magic number.'3 Is this fair? The district court in United States v. Barth did not think so. Under the old sentencing system, discretion over sentencing resided with judges. With the adoption of the Federal Sentencing Guidelines (the Guidelines ), sentencing discretion has, in effect, shifted from judges to prosecutors and even to law enforcement field agents. The agents, with little supervision, can negotiate for any amount of drugs they choose, and this amount will determine the defendant's drug sentence. Courts have developed the sentence entrapment doctrine to combat this kind of manipulation. Until recently, sentence entrapment existed largely in theory, but with the Ninth Circuit's decision in United States v. Staufer, the sentence entrapment claim has become a reality